2013
DOI: 10.1063/1.4807741
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous change in dielectric constant of CaCu3Ti4O12 under violet-to-ultraviolet irradiation

Abstract: The influence of light illumination on the dielectric constant of CaCu3Ti4O12 (CCTO) polycrystals is studied in this work. When exposed to 405-nm laser light, a reversible enhancement in the room temperature capacitance as high as 22% was observed, suggesting application of light-sensitive capacitance devices. To uncover the microscopic mechanisms mediating this change, we performed electronic structure measurements, using photoemission spectroscopy, and measured the electrical conductivity of the CCTO samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…2(a)). It was found that the O 2p state located at a binding energy around 6-8 eV was consistent with other metal oxides 25,26,34 indicating a good electrical contact between our sample and a sample holder. A counterintuitive shift of the O 2p state to lower binding energy was initially observed by the first doping condition (5 min of UV light exposure) as illustrated by the red spectrum in Fig.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…2(a)). It was found that the O 2p state located at a binding energy around 6-8 eV was consistent with other metal oxides 25,26,34 indicating a good electrical contact between our sample and a sample holder. A counterintuitive shift of the O 2p state to lower binding energy was initially observed by the first doping condition (5 min of UV light exposure) as illustrated by the red spectrum in Fig.…”
Section: Resultssupporting
confidence: 84%
“…1(b,f)) which could be described by the photogeneration of charge carriers. However, since the capacitance measured here does not instantly recover back to its original value when the irradiation is off, such changes are attributed to the creation of a thin conductive layer upon the insulating bulk referred to as a quantum-confined electron gas which is related to the creation of oxygen vacancies induced by light irradiation 26,31,32 .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Note that the change in resistance under UV irradiation of titanium oxide compounds already finds various applications as previously reported, e.g. UV detector [16], lightsensitive capacitor [17][18][19] and enhanced magnitism [20]. In the oxygen-vacancy scenario, the resistance of an insulating sample will become lower when more of oxygen vacancy is created on the SrTiO 3 surface; on the other hand, if the vacancies are healed with oxygen exposure, the resistance should become higher again.…”
Section: Resultsmentioning
confidence: 99%
“…CCTO polycrystalline ceramics can also exhibit non-Ohmic properties [12-20]. These two properties give CCTO potential for applications in capacitor and varistor devices, respectively.…”
Section: Introductionmentioning
confidence: 99%